Morphological changes of alveolar bone due to orthodontic movement of maxillary and mandibulary incisors - Pinandi Sri Pudyani; Darmawan Sutantyo; Sri Suparwitri (Dental Journal (Majalah Kedokteran Gigi), 2008)
Ideally in orthodontic tooth movement, alveolar bone will follow its movement, therefore, the ratio between bone remodeling and tooth movement is 1:1. The problem whether the ratio is valid for all kinds of tooth movement such as: tipping, torquing, or bodily, or it could be applied in tooth movement of all directions such as facially, lingually or sagitally. Various studies also showed many different ideas. Some studies state that root dehiscence and fenestration are frequently found in final orthodontic treatment and some other state that bone remodeling can compensate tooth movement. The purpose of this study was to know the changes of alveolar bone morphology caused by anterior tooth movement. The conclusion is remodeling compensation is not matched with the extension of tooth movement, thus there are many cases of root dehiscence and fenestration after orthodontic treatment.